PENGARUH DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DI KANTOR CAMAT TELUK DALAM KABUPATEN NIAS SELATAN - Prilianis Duha (Universitas Nias Raya, 2026)
The purpose of this study is to ascertain how leadership style affects worker performance in the South Nias Regency's Maniamolo Subdistrict Office. Thirty respondents make up the population and sample in this quantitative study, which uses employees as its data source. A questionnaire is used to collect data. Simple linear regression analysis is the data analysis technique that is applied. Management research findings indicate that t_count value is 10.892 > t_table 1.701. Thus, it can be said that the Maniamolo District Head Office in South Nias Regency experiences a correlation between employee performance and leadership style.. The findings of this study recommend that: (1) The Maniamolo Subdistrict Office leader should always inspire and motivate staff members so they would be motivated to work hard and enthusiastically. (2)Workers at the Maniamolo Subdistrict Office aim to do their jobs with zeal and to use their skills to the fullest extent possible to achieve the best possible results.